Автоматичне керування приготуванням живильного розчину в гідропонних теплицях - Синявський, О. Ю.; Савченко, В. В. (Energy and Automation, 2017)
AUTOMATIC CONTROL by the preparation of nutrient SOLUTION in hydroponic GREENHOUSES A. Sinyavsky, V. Savchenko The most important factors in hydroponic growing plants is acidity (pH) and total concentration of the nutrient solution to be maintained at an optimum level throughout the growing season. This is especially important in plants grown by hydroponics succinct. Now balances nutrient solutions based on chemical analyzes performed agrochemical laboratory. Readability sampling does not allow for continuous monitoring of the changing parameters of the nutrient solution and timely adjustments to it, which leads to lower yields and product quality. In this regard there was a need to develop equipment that provides preparation of nutrient solution set, control and automatic regulation of its acidity to the total concentration. The aim - to develop a system of automatic control of pH and concentration of the nutrient solution. Block greenhouses equipped soluble node where installed tanks for storage of concentrated solutions of fertilizers A and B respectively for cucumbers and tomatoes, and the storage tank of acid. From node soluble nutrient solution components submitted relevant pumps - dosing in mixing tanks controlled by valves. Then, in a mixing tank valves controlled by incoming water from the water network. Thus the nutrient solution components are presented in a strictly prescribed sequence: acid, concentrated solutions of fertilizers A and B water. The total concentration of nutrient solution is regulated by the pump dispenser in a mixing tank concentrated solutions of fertilizers and B signals for conductivity and acidity (pH) - phosphoric acid by feeding the signals. Research of parameters nutrient solution feeding concentrated solutions of fertilizers were carried out with a nutrient Zonneveld’s solution for cucumbers. Solutions fertilizers, mineral elements concentration which is 100 times higher than their value in working solution selected volume of 1 ml pipette and added to 1 liter of water. Number of added concentrated solutions changed from 0 to 10 ml. This was measured by specific conductivity of the solution conductivity KJI-1.2, acidity by ionometer И-160M. The study was conducted at a constant temperature of 25 ° C solution. When filming titration of water 30% nitric and 30% phosphoric acid from the burette, used automatic titration unit BAT-15 , the price of division which is 0.02 ml. Acid is added to 1 liter of water. Thus the measured values of conductivity and pH of the solution. The temperature of the solution is maintained constant (25 ° C). When serving in a mixing tank concentrated solution of fertilizer its electrical conductivity varies linearly. In previous acidification of water is acid does not cause a significant change in the pH value. When serving in a mixing tank acid neutralization reaction is bicarbonate, which are in the water, and the pH decreases. Electrical conductivity of nutrient solution changes slightly. Using research results change the settings nutrient solution feeding acid and concentrated solutions of fertilizers, developed a mathematical model of the acidity and concentration of the nutrient solution during its preparation. Mixing tank is two-dimensional object. Established that the bilateral cross-links can be neglected and consider regulation as rambling. Since the object management characterized as a big time delay for adjusting acidity channel and the channel adjusting its concentration and the need to separate components of the feed nutrient solution in the required sequence is the most appropriate pulse relay-law regulation. The closed system of automatic control options nutrient solution are two single-circuit systems that are primary transducers conductivity and pH regulating device pumps feed acid and concentrated solutions of fertilizers. The control device is designed based on microprocessor unit interface with sensors and actuators. It is a multi-channel controller that implements pulse law regulation ensures the implementation of logical operations and programming software led actuators. Conclusions As a result of research developed automatic control system preparing nutrient solution in hydroponic greenhouses found that acidity nutrient solution deviation from the set value does not exceed 0.2 units. pH, and its conductivity - 0.02 S / m, which corresponds to agrotechnical requirements. In this case, there was no loss of salts in the sediment. Due to the regulation of nutrient solution yield of vegetables increased by 8 – 10 % with a decrease by 10 – 15 % of the cost of fertilizers and water.